First Report Of Dpp-Iii In Plants: Its Subcellular Localization In Germinating Mung Bean (Vigna Radiata) Seeds And Distribution In Plant Parts (Applied Biological Research, 2012)
Arginyl-arginyl-4-methoxy-β-naphthylamide (Arg-Arg-4mβNA) hydro lyzeing activity is known as dipeptidylpeptidase-III (DPP-III). DPP-III  enzyme hydrolyzes various bioactive peptides, including enkephalins,  angiotensins, gastric peptides and Arg-Arg-4mβNA. We report the  presence of DPP-III enzyme in plants for the first time. The enzyme was  noticed in mung bean [Vigna radiata] seeds germinated at 25ºC for 48 h.  The crude enzyme preparation had optimum activity at alkaline pH of  8.0. Sub-cellular distribution of this enzyme revealed its cytosolic  localization. Enzyme activity when investigated in different parts of mung  bean plant revealed maximum activity in seeds followed by roots, stem  and leaves. The ubiquitous distribution of this enzyme signifies house keeping role of this enzyme in plant physiology. Maximum activity in  seeds indicates its possible role in germination.
Keywords: Arg-Arg-4-mβNA; cytosolic; DPP-III; germinating seeds Vigna radiata